2001
DOI: 10.1002/humu.1157
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoxanthoma elasticum: Point mutations in the ABCC6 gene and a large deletion including also ABCC1 and MYH11

Abstract: Pseudoxanthoma elasticum (PXE) is a mendelian disorder characterized by calcification of elastic fibers in skin, arteries, and retina. It results in dermal lesions, arterial insufficiency and retinal hemorrhages, leading to macular degeneration. PXE is transmitted either as an autosomal dominant or recessive trait and several sporadic cases have been observed. Mutations in the ABCC6 gene have been identified very recently in patients. Here, we report on a large Italian family affected by pseudoxanthoma elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Various deletions involving parts or the whole ABCC6 gene have been reported earlier. 7,[10][11][12][13][14] Small or large deletions are expected to make up for the bulk of the unidentified alleles because heterozygous middle-sized deletions are notoriously difficult to detect with traditional PCR-based assays. Furthermore, the presence of numerous repetitive elements makes the ABCC6 region subject to genomic rearrangements.…”
Section: Confirmation Of the Single-exon Deletionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various deletions involving parts or the whole ABCC6 gene have been reported earlier. 7,[10][11][12][13][14] Small or large deletions are expected to make up for the bulk of the unidentified alleles because heterozygous middle-sized deletions are notoriously difficult to detect with traditional PCR-based assays. Furthermore, the presence of numerous repetitive elements makes the ABCC6 region subject to genomic rearrangements.…”
Section: Confirmation Of the Single-exon Deletionsmentioning
confidence: 99%
“…22,23 Until now, a total of 16 different large deletions (exons, whole gene deletions) have been described. 7,[9][10][11][12][13][14] Because of the wide variety of repeat elements in the ABCC6 region, we anticipated that several of the unidentified mutant alleles in our PXE cohort would consist of deletions and insertions.…”
Section: Confirmation Of the Single-exon Deletionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a limited haplotype analysis with the microsatellite markers D16B9621 and D16S764, the five intragenic SNPs c.1841T>C, c.2490C>T, c.3803G>A, c.4404-76A>G and c.4404-31G>A and the intragenic mutation c.3421C>T, a deletion of the whole ABCC6 gene could be excluded in homozygous state in all patients and in heterozygous state in all but 2 PXE patients. Saux et al, 2001;B, Miksch et al, 2005;C, Cai et al, 2001;D, Chassaing et al, 2004;E, Meloni et al, 2001;F, Hendig et al, 2004;G, Schulz et al, 2005a;H, Hu et al, 2003;I, Uitto et al, 2001;J, Le Saux et al, 2000;K, Gheduzzi et al, 2004;L, Schulz et al, 2005b;M, Götting et al, 2004;N, Ringpfeil et al, 2000;O, Bergen et al, 2000;P, Struk et al, 2000;Q, Pulkkinen et al, 2001;R, Ringpfeil et al, 2001;S, Götting et al, 2005. F = female, M = male, wt = wild-type, hm = homozygote, ht = heterozygote, cht = compound heterozygote, nd = not determined, MSM = microsatellite marker, E = eyes, S = skin, G = gastrointestinum, H = heart, V = vascular tissue and A = arterial hypertension. a The PXE families are consecutively numbered and the affected family members are indicated by following numbers.…”
Section: Pxe Mutations Discovered By Dhplc Analysismentioning
confidence: 99%
“…In our cohort of French patients this deletion represents 9/130 (7 %) of the mutated alleles. Large deletions of the entire ABCC6 gene have been reported several times (Bergen et al, 2000;Meloni et al, 2001;Miksch et al, 2005) Exonic deletions have been identified fortuitously through failure to amplify target sequences (exon 15 and 24-25 deletions) (Le Saux et al, 2001;Katona et al, 2005) or by a SNP segregation analysis study (exon 1-21 deletion) (Miksch et al, 2005). Because large genomic rearrangements of the ABCC6 gene have not readily been detectable by conventional PCR-based techniques, it has been suggested that such mutations could account for unidentified alleles.…”
mentioning
confidence: 99%